The convergence of computational thinking, computational intelligence, and multi-agency - Coulter, Duncan Anthony (Journal of integrated design & process science, 2023)
The design of real-world industrial systems is subject to a natural tendency towards modularization in order to manage complexity. In addition, this article considers that patterns of self-similarity in many problem domains have made many such solutions naturally representable as holarchies. Likewise, the increasing need for autonomous local decision making as well as the demand to produce solutions at scale has increased the relevance of the multi-agent paradigm to the creation of modern software systems. A variety of software development patterns are explored for their compatibility with holonic multi-agency. The current skill sets required by software development workers and concomitant training activities focus on instilling computational thinking abilities, a set of related cognitive competencies useful in the development of such systems. Intelligent systems play an increasingly important role in modern development and often benefit from computational intelligence techniques for the purpose of parameter tuning. This position paper explores the intersections between holonic multi-agency, modern information systems development, the computational intelligence which train them and the computational thinking skills those developers should be trained in.